OPTIMIZATION OF THE PROCESS LOGISTICAL SUPPORT AIRLINE - Кучер, О.; Власенко, П. (Science-based technologies, 2011)
In the article were considered the questions of technological process of providing the Aircraft Maintenance Sys-tem by spare parts, instruments, equipment and materials on the base of calculation method with the goal to de-termine the quantity of spare parts on the defined operating period with limited funding.